Do you want to be my friend? - Carle, Eric (U.S.A : HarperCollins Publishers.)
"Do you want to be my friend?" asks the lonely little mouse. He follow a tail, but all he finds at its end is a rather unfriendly horse. The little mouse just wants someone to play with-but he'll have to follow a lot of tails before he can find just the right companion.
Keywords: Friendship-Fiction; Animals-Fiction